A survey of primary percutaneous coronary intervention for patients with ST segment elevation myocardial infarction in Canadian hospitals - Ko, Dennis T (Pulsus Group Inc, 2008)
BACKGROUND: Historically, access to primary percutaneous coronary intervention (PCI) for the treatment of patients with ST segment elevation myocardial infarction (STEMI) has been limited in Canada. Recent studies have identified innovative strategies to improve timely access and reduce reperfusion time. Accordingly, the contemporary use of primary PCI treatment in Canada was ascertained. METHODS: A cross-sectional survey of all 38 Canadian hospitals that were capable of performing PCI procedures was conducted from June 2007 to November 2007. The survey focused on the practice of primary PCI for patients with STEMI and whether the hospitals had implemented internal strategies to reduce ‘door-to-balloon’ times. Analyses were performed at the level of geographical regions. RESULTS: Overall, 71% of PCI hospitals (27 of 38) provided around-the-clock primary PCI for patients with STEMI, but the proportion of PCI hospitals offering this service varied widely, from 33% to 100% across regions. All Canadian PCI hospitals provided around-the-clock rescue PCI treatment to STEMI patients who had failed fibrinolytic therapy. In terms of strategies that are associated with reduced reperfusion time, it was observed that only 42% of PCI hospitals (16 of 38) provided feedback on door-to-balloon time to the emergency department and to the cardiac catheterization laboratories within one week of the primary PCI procedure. Overall, 24% of the hospitals had not adopted any of the four identified strategies to improve door-to-balloon time. CONCLUSION: Although the majority of Canadian hospitals with PCI capability provide around-the-clock primary PCI for patients with STEMI, significant variations in this practice exist across the country. Canadian PCI hospitals have not consistently adopted strategies that are associated with improved door-to-balloon time.